1992
DOI: 10.1021/bi00157a004
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional structure of a glutathione S-transferase from the Mu gene class. Structural analysis of the binary complex of isoenzyme 3-3 and glutathione at 2.2-.ANG. resolution

Abstract: The crystal structure of a mu class glutathione S-transferase (EC 2.5.1.18) from rat liver (isoenzyme 3-3) in complex with the physiological substrate glutathione (GSH) has been solved at 2.2-A resolution by multiple isomorphous replacement methods. The enzyme crystallized in the monoclinic space group C2 with unit cell dimensions of a = 87.98 A, b = 69.41 A, c = 81.34 A, and beta = 106.07 degrees. Oligonucleotide-directed site-specific mutagenesis played an important role in the solution of the structure in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
350
2
2

Year Published

1993
1993
2002
2002

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 399 publications
(366 citation statements)
references
References 48 publications
12
350
2
2
Order By: Relevance
“…Crystallographic analyses suggest that GST has the potential to dimerize (Parker et al, 1990;Reinemer et al, 1991;Ji et al, 1992). Therefore, it was important to ensure that the observed interaction in vitro was mediated by SH3, and not by GST.…”
Section: Ucs15a Binds To Proline-rich Domain Containing Protein Such mentioning
confidence: 99%
“…Crystallographic analyses suggest that GST has the potential to dimerize (Parker et al, 1990;Reinemer et al, 1991;Ji et al, 1992). Therefore, it was important to ensure that the observed interaction in vitro was mediated by SH3, and not by GST.…”
Section: Ucs15a Binds To Proline-rich Domain Containing Protein Such mentioning
confidence: 99%
“…The recent pi-and mu-class GST X-ray structures solved with bound substrate (Reinemer et al, 1991Ji et al, 1992) indicate that 81% of the residues directly contacting glutathione in domain 1 are found in the first 26 residues. This allowed us to focus on this region to develop class-specific patterns to describe the N-terminal glutathione-binding motif.…”
Section: Western Immunoblot Analysismentioning
confidence: 99%
“…et al, 1991W Wang et ai. et al, , 1992Ji et al, 1992). NMR studies also have demonstrated the similarity in structure between these classes of GSTs (Penington & Rule, 1992).…”
mentioning
confidence: 98%